2013
DOI: 10.5532/kjafm.2013.15.4.291
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Midday Air Temperature and the Solar Irradiance Over Sloping Surfaces under Cloudless Condition

Abstract: Automated weather stations were installed at 9 locations with, three different elevations, (i.e., 50m, 100m, and 300m a.s.l.) with different slope and aspect in a small watershed (50km 2 area). Air temperature at 1500 LST and solar radiation accumulated for 1100-1500 LST were collected from January to December 2012. Topography of the study area was defined by a 30 × 30 m digital elevation model (DEM) grid. Accumulated solar irradiance was calculated for each location with the spatially averaged slope and aspec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…The daily maximum temperature estimates to which only the lapse rate correction was applied ('control') were reportedly different from the measured temperatures (Kim and Yun, 2013). Previous studies have concluded that the primary cause of error was the solar radiation effect.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The daily maximum temperature estimates to which only the lapse rate correction was applied ('control') were reportedly different from the measured temperatures (Kim and Yun, 2013). Previous studies have concluded that the primary cause of error was the solar radiation effect.…”
Section: Resultsmentioning
confidence: 99%
“…If any grid cell is shaded by a neighboring cell, then that cell does not receive any direct beam radiation, even though the solar altitude is above the horizon for that cell. In this process, the topography of the study area was represented by a 30 m × 30 m digital elevation model (DEM), but areas smoothed to a radius of 750 m (i.e., 25 DEM cells) were used for the slope and aspect calculations following the suggestion by Kim and Yun (2013). The hourly solar irradiance calculated with Eq.…”
Section: A Study Area and Data Acquisitionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this process, the topography of the study area was represented by the 30-m DEM, but areas smoothed to a radius of 750 m (i.e., 25 DEM cells) were used for the slope and aspect calculation following the suggestion of Kim and Yun (2013). Extraterrestrial daily radiation was estimated for the center of the study area (35° 10' 00"N and 127° 43' 00"E) from January 1 to December 31 using the method of Allen et al (1998), and the same value was used regardless of the site location.…”
Section: Validation Of Temperature Estimatesmentioning
confidence: 99%